Analisa Percepatan Proyek Pembuatan Mesin Grinding Cat Dengan Time Cost Trade Off Method (Studi Kasus : PT TDI Sidoarjo) - Abdullah, Safira Azham; Singgih, Mochammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The case study in this research is a project to manufacture a paint paste grinding machine at PT Pabrik Cat Tunggal Djaja Indah. In its implementation, this project is considered to have a delay of 2 weeks, with a total project completion time of 120 days, so project acceleration is needed. The scheduling method is carried out using PDM (Precendence Diagram Method) with the help of Microsoft Project 2016 software to find the critical path, then after knowing the critical activities, crashing is carried out with the alternative of adding working hours or overtime and adding optimum workers. The Time Cost Trade Off method will analyze the time after crashing. The optimal duration to complete this project is 107 days with an acceleration of 13 working days with a percentage of 10.38% and an optimal total cost of Rp 262,947,693 with a cost efficiency of 3.56%.